2020
DOI: 10.1101/2020.07.13.201830
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enrofloxacin shifts intestinal microbiota and metabolic profiling and hinders recovery fromSalmonella entericasubsp.entericaserovarTyphimuriuminfection in neonatal chickens

Abstract: Enrofloxacin is an important antibiotic used for prevention and treatment of Salmonella infection in poultry in many countries. However, oral administration of enrofloxacin may lead to the alterations in the microbiota and metabolome in the chicks intestine, thereby reducing colonization resistance to the Salmonella infection. To study the effects of enrofloxacin on chicken cecal Salmonella, we used different concentrations of enrofloxacin to feed 1-day-old chickens, followed by oral challenge with Salmonella … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…With the widespread use of antibiotics, diseases caused by MDR strains have become increasingly difficult to handle, especially those caused by Enterobacteriaceae, including Salmonella, Escherichia coli, Shigella, and Pseudomonas. 1,2 Hence, new antibacterial drugs are urgently needed for clinical treatment and food preservation.…”
Section: Introductionmentioning
confidence: 99%
“…With the widespread use of antibiotics, diseases caused by MDR strains have become increasingly difficult to handle, especially those caused by Enterobacteriaceae, including Salmonella, Escherichia coli, Shigella, and Pseudomonas. 1,2 Hence, new antibacterial drugs are urgently needed for clinical treatment and food preservation.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal exposure to environmental antibiotics during the gravid period predicted gastrointestinal effects in zebrafish offspring (Qiu, Liu, et al, 2020). Ma et al (2020) found that ENR exposure shifted the intestinal microbiota and metabolic profiling and hindered recovery from Salmonella enterica subsp. Romick‐Rosendale et al (2009) found that eight metabolites changed through NMR‐based metabonomic analysis of mouse urine and faecal extracts following oral treatment with the broad‐spectrum antibiotic ENR.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, feces metabolites may also re ect the physiological status of calves [38,39]. Currently, LC-MS based metabolomics analyses are being increasingly performed to explore the alteration of metabolites [40].…”
Section: Discussionmentioning
confidence: 99%